Ad hoc networks capacity scaling problem - Adisa Hasković Džubur; Alem Čolaković; Belma Memić; Elma Avdagić-Golub (Science, Engineering and Technology, 2021)
A large number of researchers found their interest in addressing the issue of capacity scaling for wireless ad hoc networks. This paper aims to provide a comprehensive overview of the development of capacity scaling laws in wireless networks, highlighting the problem of scaling as one of the basic challenges in their research. The review began with the definition of the notion of bandwidth of random networks, which were taken as a reference model of consideration when determining more advanced strategies for improving throughput capacity. Based on these strategies, other factors that have an impact on capacity scaling laws have been identified and elaborated. Finally, the capacity of hybrid wireless networks, ie networks in which at least two types of nodes functionally exist (ad hoc nodes/infrastructure nodes / auxiliary nodes), was partially investigated.